(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2024)
Drift is a common phenomenon in aquatic ecosystems. Macroinvertebrate communities use it for the colonization of new habitats. The objective of this study was to evaluate the drift of aquatic macroinvertebrates during a daily cycle in three different flow regimes: low, medium, and high, in the middle zone of the Tota River, Boyacá. The material was daily collected, using nine drift nets (200 - 250 μm pore size) per sampling. In the three periods, only dissolved oxygen (mg/l), temperature (°C), and phosphates (PO4+mg/l) showed significant differences. The most representative derived orders in the different sampling periods were Diptera and Ephemeroptera during the diurnal cycle; However, for times of low water Trichoptera, Plecoptera, and Ephemeroptera dominated the drift in the nocturnal cycle. The hydrological and physicochemical conditions of the river influence the drifting dominance patterns of organisms that vary throughout the daily cycle. In the low-water nocturnal cycle, the drift was dominated by insects such as Trichoptera that are sensitive to light and temperature, as well as Plecoptera, which, due to its larger size, in order to avoid predators. Furthermore, smaller Ephemeroptera individuals showed aperiodic behavior, suggesting the influence of additional factors in their movement.